Pengaruh Content Marketing Of Tiktok Dan E-Wom Terhadap Brand Awareness Dan Minat Beli Produk Umkm Sektor Kuliner Di Kabupaten Pasuruan - Miftahul Huda (Universitas Hamzanwadi, 2022)
The purpose of this study was to determine and measure the effect of content marketing of TikTok and E-WOM on brand awareness and purchase intention in UMKM products in the culinary sector in Pasuruan Regency. This study is a quantitative study with a sample of 115 respondents using a purposive sampling technique with an analytical tool, namely SPSS version 26. The results showed that Content Marketing of TikTok had a significant effect on Brand Awareness, E-WOM had a significant effect on Brand Awareness, Content Marketing of TikTok had a significant effect on Purchase Intention, E-WOM had a significant effect on Purchase Intention and Brand Awareness had a significant effect on Purchase Intention. Content Marketing TikTok through Brand Awareness has a significant effect on Purchase Intention and E-WOM through Brand Awareness has a significant effect on Purchase Intention